Modern Georgian Terminology - Karosanidze, Lia (Actual Problems of Kartvelology, 2013)
It is a well-known fact that norms of any literary language are determined by a live language but, apart from that, the literary language is directly linked to the development of the scientific language and its direction, in general. If the scientific circles take care of the language, create terminology based on the current vocabulary of the Georgian language or the materials of ancient Georgian literature, the language develops properly. Most terms gradually become natural parts of the literary language. Consequences of the 11thand 12th-century linguistic policy of translators are the words like these: goni (mind), goniereba (consciousness), arsi (essence), metsniereba (science), vitareba (condition), gantsda (feeling), khedva (look), etc. Georgian philosophical, grammatical, mathematical terms were created during this period. Unfortunately, the process of development of the scientific language created by old Georgian translators stopped in the following century, followed by incursion of Eastern (Turkish-Persian) vocabulary during the 13-17th centuries. The process of creating Georgian terms led by Ilia Chavchavadze in the 19th century continued in the 20th century as well. Russian-Georgian dictionary of technical terms, which was published in 1920, is extremely interesting for the history of Georgian terminology. We can witness Georgian language becoming poor, strange and unnatural for us. Many people notice and speak about this problem but, unfortunately, everybody tries to solve it on their own. Creating terminology is a public rather than private issue. Modern Georgian scientific society is not united across one problem and individuals cannot save the language on their own. Some people are against sharing the experience of the past. We regard that those who try to go forward without considering the past, should definitely expect failure. There is no use creating something new and unusual while ignoring the work of schools responsible for creating Georgian terminology. Innovation based on the rich historical heritage is the path of contemporary terminology today. And the proper creation of Georgian terminology is the future of Georgian language.